Magnetization reversal mechanism in patterned (square to wave-like) Py antidot lattices. (1st December 2016) - Tahir, N; Zelent, M; Gieniusz, R; Krawczyk, M; Maziewski, A; Wojciechowski, T; Ding, J; Adeyeye, A O
Abstract: The effects of shape and geometry of antidot (square, bi-component, and wave-like) lattices (ADLs) on the magnetization reversal processes and magnetic anisotropy has been systematically investigated by magneto-optical Kerr effect based microscopy. Our experimental results were reproduced by micromagnetic simulations, which highlight the qualitative agreement with the experimental results. We have demonstrated that a small antidot in the center of a unit cell in the square ADL is sufficient to induce additional easy axes with large coercive fields. In wave-like patterns, narrow channels connecting smaller and larger antidots (bi-component ADL) further drastically change the anisotropy map, creating the high coercive fields along a wide angular range (90°) of directions parallel to the channels. In simulated results, we have observed formation of periodic domain structures in all ADLs, however, in the case of a wave-like pattern it is most regular and moreover two different periodic patterns are stabilized at different applied magnetic field values. The formation of 360° domain walls were also observed in wave-like ADL where these domains are formed along the lines connecting adjacent larger and smaller antidots, perpendicular to the channels. These findings point out the possibility of exploiting ADLs with complex unit cells in magnonic or spintronic applications.